The Role of Generative Artificial Intelligence in Shaping Critical Thinking Skills Among Undergraduates - Jegashini, K.; Shivany, S. (TASME, 2025)
This study aims to explore the influence of generative artificial intelligence (AI) tool, namely ChatGPT, on the development of undergraduate students' critical thinking skills. Although existing literature has a tendency to discuss either the ethical concerns or performance-based implications of AI integration in learning to a large extent, a significant knowledge gap in the literature pertains to how generative AI affects students' cognitive engagement and critical thinking processes. This research bridges that gap by analysing whether AI is a facilitating learning tool or promotes overreliance and superficial thinking. This offers new insights by positioning AI not merely as a technological tool but as a cognitive partner that is capable of reshaping traditional learning tendencies. This study applied a qualitative design and semi-structured interviews to gain an in-depth understanding of how Faculty of Management Studies …